A national survey of the impact of rapid scale-up of antiretroviral therapy on health-care workers in Malawi: effects on human resources and survival - Simon D Makombe; Andreas Jahn; Hannock Tweya; Stuart Chuka; Joseph Kwong-Leung Yu; Mindy Hochgesang; John Aberle-Grasse; Olesi Pasulani; Erik J Schouten; Kelita Kamoto; Anthony D Harries
OBJECTIVE: To assess the human resources impact of Malawi's rapidly growing antiretroviral therapy (ART) programme and balance this against the survival benefit of health-care workers who have accessed ART themselves. METHODS: We conducted a national cross-sectional survey of the human resource allocation in all public-sector health facilities providing ART in mid-2006. We also undertook a survival analysis of health-care workers who had accessed ART in public and private facilities by 30 June 2006, using data from the national ART monitoring and evaluation system. FINDINGS: By 30 June 2006, 59 581 patients had accessed ART from 95 public and 28 private facilities. The public sites provided ART services on 2.4 days per week on average, requiring 7% of the clinician workforce, 3% of the nursing workforce and 24% of the ward clerk workforce available at the facilities. We identified 1024 health-care workers in the national ART-patient cohort (2% of all ART patients). The probabilities for survival on ART at 6 months, 12 months and 18 months were 85%, 81% and 78%, respectively. An estimated 250 health-care workers' lives were saved 12 months after ART initiation. Their combined work-time of more than 1000 staff-days per week was equivalent to the human resources required to provide ART at the national level. CONCLUSION: A large number of ART patients in Malawi are managed by a small proportion of the health-care workforce. Many health-care workers have accessed ART with good treatment outcomes. Currently, staffing required for ART balances against health-care workers' lives saved through treatment, although this may change in the future.